Advancements in lentil breeding: harnessing molecular markers and omics approaches for resistance to biotic and abiotic stresses - Yeken, Mehmet Zahit; Tekin, Mehmet; Ali, Amjad; Altaf, Muhammad Tanveer; Qureshi, Sarmad Ali; Celik, Ali; Sarikaya, Meliha Feryal (Csiro Publishing, 2025)
Lentil (Lens culinaris Medik.), an essential cool-season legume crop, is widely cultivated in southern Asia as a sole winter crop following the rice harvest. It is highly valued for its rich nutritional profile, including abundant protein, folic acid, iron, and zinc. However, lentil production is severely threatened by various abiotic and biotic stresses. Key abiotic stresses include heat, drought, salinity, heavy metal toxicity, and iron deficiency. In contrast, biotic stresses comprise anthracnose, ascochyta blight, sclerotinia white mold, fusarium wilt, rust, and various viral, bacterial, and nematode diseases. To combat these challenges, plant breeders and geneticists have focused on identifying resistant germplasm, deciphering the genetic basis of resistance, and mapping associated resistance genes. Significant progress in lentil genomics, with efforts to establish a unified genetic map, has significantly enhanced breeding strategies. Presently, molecular breeding, specifically targeting anthracnose and ascochyta blight in Australia and Canada, has yielded promising results. Furthermore, the advent of molecular markers and genomics has revolutionized lentil breeding, enabling the precise development of disease-resistant and climate-resilient lentil varieties through marker-assisted selection. In addition, the integration of omics tools, such as genomics, transcriptomics, proteomics, and metabolomics, has provided deeper insights into the complex biological pathways underlying stress tolerance. These technologies allow for more comprehensive identification of candidate genes and biomarkers, further advancing lentil breeding efforts. This review highlights the integration of traditional and innovative breeding techniques to address emerging challenges, particularly in the context of climate change. By combining ancestral knowledge with modern molecular breeding tools, researchers are making substantial progress in developing robust lentil varieties with improved resistance to abiotic and biotic stresses.
Keywords: climatic factors; DNA markers; lentil breeding; marker-assisted selection; omic tools; plant genomic; QTLs mapping; trait pyramiding